Functioning of the EROS-R Scale in a Clinical Sample of Psychiatric Patients: New Psychometric Evidence from the Classical Test Theory and the Item Response Theory - Vilca, Lindsey W. (2022)
“Reliable and valid assessment instruments that can be applied briefly and easily in clinical and outpatient settings that provide information about the sources of reinforcement that the patient finds in his life are especially relevant in therapy. The study aimed to evaluate the psychometric properties of the Environmental Reward Observation Scale (EROS-R) in a sample of psychiatric patients. A sample of 228 psychiatric patients of both sexes (56.1% men and 43.9% women) aged between 18 and 70 years was selected. Along with the EROS-R, other instruments were administered to assess depression and anxiety. The results show that the scale fits a unidimensional model, presenting adequate fit indices (RMSEA = 0.077 (IC 90% 0.055–0.100); SRMR = 0.048; CFI = 0.98; TLI = 0.98). It was also shown that the degree of reward provided by the environment (EROS-R) correlates negatively with the level of depression (ρ = −0.54; p < 0.01) and anxiety (ρ = −0.34; p < 0.01). From the IRT perspective, all the items present adequate discrimination indices, where item 4 is the most precise indicator to measure the degree of environmental reward. All this leads us to conclude that the EROS-R is an instrument with robust psychometric guarantees from TCT and IRT’s perspectives, making it suitable for use in clinical contexts“